2019
DOI: 10.1108/apjml-07-2018-0261
|View full text |Cite
|
Sign up to set email alerts
|

Comparison-based perceived attribute performance as a better antecedent of satisfaction, value and loyalty

Abstract: Purpose Product performance measurements have been used to explain other business performance variables. The purpose of this paper is to propose that, regarding Mexican consumers, the “comparison-based perceived attribute performance” (CAP) approach is a better predictor of outcomes, such as satisfaction, value and loyalty, compared with the traditional measurement of “non-comparison-based perceived attribute performance” (NCAP). These two forms of assessing attribute-level performance may be considered as dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…On this basis, CFS was used in this study. Satisfaction's relationship to loyalty is well documented (Anderson et al, 1994;Bodet, 2008;Brunner et al, 2008;Kumar et al, 2013;Vera-Martinez and Ornelas, 2019), where cumulative satisfaction is antecedent to loyalty (Oliver, 1999). We argue that CFS is the better predictor of loyalty than transaction-specific satisfaction (Bodet, 2008;Koenigstorfer et al, 2010;Olsen and Johnson, 2003) for the sports context, where research has found cumulative satisfaction to be positively related to attitudinal and behavioural fan loyalty (Biscaia et al, 2012(Biscaia et al, , 2017Clemes et al, 2011;Gray and Wert-Gray, 2012).…”
Section: Cumulative Fan Satisfactionmentioning
confidence: 77%
“…On this basis, CFS was used in this study. Satisfaction's relationship to loyalty is well documented (Anderson et al, 1994;Bodet, 2008;Brunner et al, 2008;Kumar et al, 2013;Vera-Martinez and Ornelas, 2019), where cumulative satisfaction is antecedent to loyalty (Oliver, 1999). We argue that CFS is the better predictor of loyalty than transaction-specific satisfaction (Bodet, 2008;Koenigstorfer et al, 2010;Olsen and Johnson, 2003) for the sports context, where research has found cumulative satisfaction to be positively related to attitudinal and behavioural fan loyalty (Biscaia et al, 2012(Biscaia et al, , 2017Clemes et al, 2011;Gray and Wert-Gray, 2012).…”
Section: Cumulative Fan Satisfactionmentioning
confidence: 77%
“…Chen and Wang (2009) stated that a major reason for customers to continue a relationship with a company is their positive evaluation of customers of the received products or services. The findings of many studies indicated the impact of CS on loyalty (Pic on et al, 2014;Thaichon and Quach, 2015;Vera-Martinez and Ornelas, 2019). For instance, the literature in consumer behaviour confirmed that when customers are satisfied, they are more likely to repeat buying goods and services and show loyalty in comparison with unsatisfied customers (Thaichon and Quach, 2015).…”
Section: Storescape and Customer Loyaltymentioning
confidence: 98%
“…When a customer has a positive attitude toward a brand, he/she will have a strong preference and bring a lot of satisfaction and loyalty Manohar, 2017;Ganesan et al, 2017;Vera-Martinez and Ornelas, 2019). Though existing literature indicates a positive relationship between brand attitude and various dimensions of brand equity, there is a dearth of literature indicating empirically the effect of one variable on the other.…”
Section: Brand Attitude Leads To Brand Equitymentioning
confidence: 99%